Chromosome banding in three species of Hypsiboas (Hylidae, Hylinae), with special reference to a new case of B-chromosome in anuran frogs and to the reduction of the diploid number of 2n=24 to 2n=22 in the genus - Gruber, Simone Lilian; Baptista Haddad, Celio Fernando; Kasahara, Sanae (Springer, 2007)
The chromosomes of hylids Hypsiboas albopunctatus, H. raniceps, and H. crepitans from Brazil were analyzed with standard and differential staining techniques. The former species presented 2n = 22 and 2n = 23 karyotypes, the odd diploid number is due to the presence of an extra element interpreted as B chromosome. Although morphologically very similar to the small-sized chromosomes of the A complement, the B was promptly recognized, even under standard staining, on the basis of some characteristics that are usually attributed to this particular class of chromosomes. The two other species have 2n = 24, which is the chromosome number usually found in the species of Hypsiboas karyotyped so far. This means that 2n = 22 is a deviant diploid number, resulted from a structural rearrangement, altering the chromosome number of 2n = 24 to 2n = 22. Based on new chromosome data, some possibilities were evaluated for the origin of B chromosome in Hypsiboas albopunctatus, as well as the karyotypic evolution in the genus, leading to the reduction in the diploid number of 2n = 24 to 2n = 22.
Keywords: Ag-NOR; BrdU incorporation; C banding; fluorochrome staining; replication banding; supernumerary chromosome